Pengaruh Opini, Reputasi KAP, COSO Framework, Laba, dan Struktur Modal terhadap Tingkat Kepercayaan Investor - Valencia, Jessica; Samuel Wirawan; Amelia Setiawan; Hamfri Djajadikerta (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to determine the effect of audit opinion, reputation of public accountant firms, the implementation of COSO framework, net income, and capital structure on the level of investor confidence. In this study, multiple linear regression analysis model was used to determine the effect between independent variables on the level of investor confidence, besides that, descriptive statistical analysis, classical assumption test, partial effect test, simultaneous effect test, and coefficient of determination test will also be carried out. The level of investor confidence will be described by the stock price of a company. The share price will take a number from the closing price on December 31 of each year. There were 4 samples of companies from the infrastructure, utilities, and transportation sectors and data obtained from 2011 to 2021 tested in this study. The four companies are AirAsia Indonesia Tbk, Leyand International Tbk, Steady Safe Tbk, and Garuda Indonesia Tbk.  The results of the study indicate that the audit opinion variable, the application of the COSO Framework, net income, and capital structure can not be proven to have a partial influence on the level of investor confidence. However, the variable reputation of public accountant firms has a partial influence on the level of investor confidence. For the four independent variables themselves have a simultaneous influence on the investor confidence. A high level of investor confidence is coveted by all companies. The higher the investor's trust, the higher capital that can be used by the company for operational activities. Every company is flocking to increase its value in order to gain strong investor confidence. The components studied are audit opinion, KAP reputation, COSO Framework, net income, and capital structure on the level of investor confidence in the infrastructure, utilities and transportation industries. In this study, multiple linear regression analysis model was used to determine the effect between independent variables on the level of investor confidence, besides that, descriptive statistical analysis, classical assumption test, partial effect test, simultaneous effect test, and coefficient of determination test will also be carried out. The level of investor confidence described by the stock price of a company. The share price will take a number from the closing price on December 31 of each year. There were 4 samples of companies from infrastructure, utilities, and transportation sectors and data obtained from 2011 to 2021 tested in this study. The four companies are AirAsia Indonesia Tbk, Leyand International Tbk, Steady Safe Tbk, and Garuda Indonesia Tbk.  The results of the study indicate that the audit opinion variable, COSO Framework, net income, and capital structure can not be proven to have a partial influence on the level of investor confidence. However, the variable KAP reputation has a partial influence on the level of investor confidence. For the four independent variables themselves have  simultaneous influence on the investor confidence.